Psychometric properties of the influences on planning decision-making in physical education questionnaire (CIPEF) - Viciana Ramírez, Jesús; Blanco Vega, Humberto; Mayorga Vega, Daniel (Cuadernos de Psicología del Deporte, 2015)
The present study analyzes the psychometric properties of the Influences on the Planning Decision-Making in Physical Education Questionnaire (CIPEF). Literature had contributed instruments for measuring beliefs and value orientations toward Physical Education, but there are no instruments that measure the in"uence of speci$c factors on teachers’ decision-making when planning Physical Education. Method. The sample consisted of 335 Andalusian teachers (238 men and 97 women, average age= 29.85 ± 10.94 years). Exploratory and confirmatory analyses were conducted in order to analyze the factorial structure of the questionnaire. The results showed the viability and adequacy of an eight-factor structure (curriculum standards, preservice training, physical environment, teaching experiences, physical activities experiences, socialization by other teachers, material and equipment, and level of preparation in the subject matters) with adequate fit indices of reliability and validity, and showing strong evidences of stability of the obtained factorial structure. Discussion. This instrument could be used in the analysis of teachers’ planning decision-making, which has been studied mainly through qualitative approaches up till now. Further research is recommended in order to corroborate these findings.